Principles of Using Cl/Br, B/Br and Na/K Ratios to Clarify the Genesis of Natural Waters - T. A. Kireeva (Georesursy, 2024)
The principles of using chlorine-bromine (Cl/ Br), boron-bromine (B/Br) and sodium-potassium (Na/K) ratios to determine the genesis of aqueous solutions are substantiated. Examples are given of clarifying the origin of waters, both natural and man-made, based on the relationship between the values of these coefficients and the mineralization of solutions (Mtot). It is shown that different values of the Cl/ Br coefficient make it possible not only to identify the difference between natural brines of concentration and brines of dissolution of halite strata, but also to identify groundwater contaminated with technogenic brines of hydrochloric acid treatments. Using the ratio B/Br > 1 makes it possible to diagnose the influx of high-temperature ( >100 °C) waters into deep aquifers, and is also a sign of the release of technogenic condensate waters. The value of the Na/K ratio, if reduced to 1 or less, makes it possible to reliably diagnose both technogenic brines and technogenically polluted fresh waters.